Biocompatibility Evaluation of Electrospun Scaffolds of Poly (L-Lactide) with Pure and Grafted Hydroxyapatite - Luis Jesús Villarreal-Gómez (Journal of the Mexican Chemical Society, 2014)
The objective of this work was to evaluate the biocompat - ibility of scaffolds of poly( L -lactide) with pure and grafted hydroxyap - atite, at various concentrations of reinforcement. The biocompatibility tests were carried out in vivo in Wistar rats by implanting the material into the subcutaneous and muscle tissues from 1 to 14 weeks and evaluating the surrounding tissue stained with hematoxylin-eosin. For in vitro assays, MTT and neutral red assay were used to evaluate any cytotoxicity in Mioblast Muscle C2C12 Cells (ATCC® CRL-1772™) and Bovine Coronary Artery Endothelial Cells (BCAEC); Escherichia coli and Staphylococcus aureus were used to evaluate bacterial adhe - sion. All variants of scaffolds provoked a mild inflammatory response, without showing necrosis. No evidence of cytotoxicity was presented in cell viability tests and good bacterial cell adhesion was visualized for all of the materials studied.